MORFOMETRI BURUNG DIURNAL DI KAWASAN HUTAN LINDUNG DESA SEKENDAL KECAMATAN AIR BESAR KABUPATEN LANDAK KALIMANTAN BARAT - Nurmala, Maya; Erianto, .; Dirhamsyah, M (JURNAL HUTAN LESTARI, 2017)
Morphometrics is a way to see the form, structure, and measurement of body parts, the outer forms of certain body parts that are relied upon to compare. This research aimed to know the diurnal bird’s morphometry in protected forest of sekendal village in Air Besar Sub-District. The methods used in this research was the capture-recapture method by using mist nets, and mixed method on the Transect and the Point Count method on the observations made with a length of 1000 M with a radius of 50 M at any points, the distance between points was 200M. Based on the result of observation, there were 44 bird species caught in a mist net, then the result of observation there were 52 types of birds and a number of birds caught in the mist net were 22 species. Based on observations, it can be described that the protected forest of Sekendal village in Air Besar sub-district is one of the habitats for wildlife, especially wildlife of birds, but the condition of the habitat needs to be noticed in order to maintain the existence of wildlife of birds. There were some disruptions on the location of the research which are can threaten the existence of this wildlife such as forest fires and the hunting activity. Keywords: Diurnal bird, Morphometry, Protected forest